2018
DOI: 10.1080/21645515.2018.1496764
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability, and immunogenicity of a novel 4-antigen Staphylococcus aureus vaccine (SA4Ag) in healthy Japanese adults

Abstract: A novel Staphylococcus aureus 4-antigen vaccine (SA4Ag) is under development, comprising capsular polysaccharide serotypes 5 and 8 (CP5 and CP8) conjugated to CRM, recombinant protein clumping factor A (rmClfA), and recombinant manganese transporter protein C (MntC). We evaluated SA4Ag safety, tolerability, and immunogenicity in Japanese adults aged 20 to 64 and 65 to 85 years. A total of 136 healthy Japanese adults (68 per age group) were randomized 1:1 to receive single-dose SA4Ag or placebo intramuscularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Opsonic antibodies represent a reliable correlate of protection for several other vaccines such as pneumococcal, meningococcal and H. influenzae vaccines (7). Remarkably, all the SA vaccines advanced into clinic were strong inducers of antibodies that promoted opsonophagocytic activity (8)(9)(10), putting in question whether the paradigm of opsonic antibodies as correlate of immunity can be applied to SA. In the case of one of these vaccine candidates, the single component vaccine consisting of the iron-regulated protein IsdB (V710, Merck), the trial was stopped due to safety concerns after ∼8,000 patients undergoing cardiothoracic surgery were recruited.…”
Section: Introductionmentioning
confidence: 99%
“…Opsonic antibodies represent a reliable correlate of protection for several other vaccines such as pneumococcal, meningococcal and H. influenzae vaccines (7). Remarkably, all the SA vaccines advanced into clinic were strong inducers of antibodies that promoted opsonophagocytic activity (8)(9)(10), putting in question whether the paradigm of opsonic antibodies as correlate of immunity can be applied to SA. In the case of one of these vaccine candidates, the single component vaccine consisting of the iron-regulated protein IsdB (V710, Merck), the trial was stopped due to safety concerns after ∼8,000 patients undergoing cardiothoracic surgery were recruited.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a recent study showed that SA4Ag leads to persistent functional immune responses against S. aureus antigens throughout 36 months in healthy adults [39]. Also, further investigation showed that SA4Ag showed an acceptable safety profile and induced rapid and robust functional immune responses in the 20 to 64 and 65 to 85 years groups [40]. This vaccine also showed good results against the progressive condition of S. aureus infection in an animal study.…”
Section: On-going Clinical Human Vaccine Trialsmentioning
confidence: 91%
“…The most noteworthy of these is the phase IIb failure of Pfizer's SA4Ag vaccine candidate. Composed of recombinant MntC, ClfA and both CP5 and CP8, each conjugated to a detoxified form of diphtheria toxin, this vaccine was tested in four phase I clinical trials (20,(139)(140)(141) before ultimately failing to reach designated protection endpoints in a subsequent efficacy trial (NCT02388165). In phase I trials, a single dose of vaccine was sufficient to elicit high titers of specific and functional antibody responses in recipients from age 18-80 shown to last for at least a year after vaccination.…”
Section: An Update Regarding Ongoing and Recently Concluded Clinical Trials For S Aureus Vaccinesmentioning
confidence: 99%